In vitro propagation of Gladiolus dalenii from the callus through the culture of corm slices - Ahmad Nazri Karim Mamun, Farhana Yesmin, Sreeramanan Subramaniam, Md. Humayun Kabir (Journal of Phytology, 2016)
Production of sufficient numbers of plants of a unique genotype is possible using in vitro culture system. In this study, the effects of various concentrations and combinations of plant growth regulators for in vitro regeneration of gladiolus were used with corm fractions as explants. Thus, an efficient in vitro propagation method was developed for Gladiolus dalenii using corm slices as explants. The highest rate of 90% explants for callus induction was observed on MS medium supplemented with 7.5 mg/L NAA after culture initiation of 90 days. Calli responded to form well developed shoots on transferring to medium containing MS + 0.5 mg/L BA + 0.5 mg/L Kin, in which 70% of the cultured calli responded to produce shoots. The average number of shoot per culture calli was 20 ± 2.40 and the average shoot lengths of 4.50 ± 0.45 cm were achieved in this medium after culture of 60 days. Recurrent callus induction and continuous plant regeneration were also observed in the same medium during the passage of shoot induction period. Shoots rooted well when they were excised individually and implanted on half-strength MS medium supplemented with 2.5 mg/L IBA, which resulted 90% shoot induced roots after culture of 30 days. The average number of root per shoot was 10 ± 1.20 and the average root length of 5.5 ± 0.70 cm was observed in this medium. Eighty percent (80) of the in vitro raised plantlets were survived in the natural environment.